Mouth Puffing Phenomenon and Upper Airway Features May Be Used to Predict the Severity of Obstructive Sleep Apnea - Jau JY; Kuo TB; Li LPH; Chen TY; Hsu YS; Lai CT; Yue WC; Huang PH; Yang CC (Nature and Science of Sleep, 2023)
Je-Yang Jau,1 Terry BJ Kuo,1– 3 Lieber PH Li,1,4– 6 Tien-Yu Chen,1,7 Ying-Shuo Hsu,1,8,9 Chun-Ting Lai,1,2 Weng-Cheu Yue,10 Pin-Hsuan Huang,11 Cheryl CH Yang1,2,4,12,13 1Institute of Brain Science, National Yang-Ming Chiao-Tung University, Taipei, Taiwan; 2Sleep Research Center, National Yang Ming Chiao Tung University, Taipei, Taiwan; 3Tsoutun Psychiatric Center, Ministry of Health and Welfare, Nantou, Taiwan; 4Department of Otolaryngology, Cheng Hsin General Hospital, Taipei, Taiwan; 5Department of Medical Research, China Medical University Hospital, China Medical University, Taichung, Taiwan; 6Department of Speech Language Pathology and Audiology, College of Health Technology, National Taipei University of Nursing and Health Sciences, Taipei, Taiwan; 7Department of Psychiatry, Tri-Service General Hospital, School of Medicine, National Defense Medical Center, Taipei, Taiwan; 8Department of Otolaryngology, Shin Kong Wu Ho-Su Memorial Hospital, Taipei, Taiwan; 9School of Medicine, Fu Jen Catholic University, New Taipei City, Taiwan; 10DP Dental, Singapore; 11Department of Health Promotion and Health Education, National Taiwan Normal University, Taipei, Taiwan; 12Department of Education and Research, Taipei City Hospital, Taipei, Taiwan; 13Brain Research Center, National Yang Ming Chiao Tung University, Taipei, TaiwanCorrespondence: Cheryl CH Yang, Institute of Brain Science, National Yang-Ming Chiao-Tung University, No. 155, Sec. 2, Li-Nong St., Beitou, Taipei, 11221, Taiwan, Tel +886-2-28267058, Fax +886-2-28273123, Email cchyang@ym.edu.tw Lieber PH Li, Department of Otolaryngology, Cheng Hsin General Hospital, No. 45, Cheng Hsin St., Beitou, Taipei, 11221, Taiwan, Tel +886-2-28264400, Email lieber.chgh@gmail.comPurpose: This study aimed to investigate (1) the role of mouth puffing phenomenon and upper airway features in obstructive sleep apnea (OSA) and (2) whether mouth-taping during sleep alleviated the severity of OSA.Participants and Methods: Seventy-one participants underwent a two-night home sleep test (the first day sleeping normally; the second day sleeping with their mouths being taped); their oximetry desaturation index (ODI) and mouth puffing signals (non-mouth puffing, complete mouth puffing, intermittent mouth puffing (IMP), and side mouth puffing) were detected by a validated fingertip pulse oximeter and a mouth puffing detector. The participants were grouped into the ODI-improved group and the ODI-not-improved group according to their sleeping test results. The radiograph was taken by cone-beam computed tomography and cephalometries. Upper airway features including airways, soft tissues, and oral cavity variables were measured.Results: Participants with severe OSA showed a higher IMP percentage compared with those with normal, mild, and moderate OSA (severe: 33.78%, moderate: 22.38%, mild: 14.55%, normal: 0.31%, p < 0.001). In all participants, the ODI and the percentage of SpO2 under 90 (T90) were positively related to body mass index (BMI) (r = 0.310 and 0.333, respectively), while ODI and T90 were negatively correlated with the minimum width of the airway (r = − 0.473 and − 0.474, respectively); all mentioned relationships were significant (p < 0.05).Conclusion: IMP proportions were found to be higher in the half of participants whose ODI did not improve after mouth-taping and in those with severe OSA. Moreover, OSA patients with higher ODI, higher T90, and higher proportions of IMP were more likely to have a narrower upper airway.Keywords: mouth breathing, mouth puffing, sleep phenomena, oximeter, sleep apnea, accelerometer